Use of Mobile Phone Applications by Farmers in North-West Nigeria - Abdullahi Abubakar Khidir; Oladimeji Idowu Oladele; Olayinka Jelili Yusuf (Journal of Agricultural Extension, 2019)
This study investigated awareness about and determinants of use of mobile phone applications among farmers in North-West Nigeria. The multi-stage sampling procedure was used to select 385 respondents for the study. Data were collected through the use of pre-tested structured questionnaires and summarized using frequency counts, percentages, mean and standard deviation. The Tobit regression model was used for inferential deduction. The results show that the Majority (96%) owned a mobile phone. 100% and 97% were aware of the call app and SMS app, respectively. Majority of farmers were generally not aware and did not use most mobile apps, with exception of call and SMS apps. The majority (96% and 59%) used the call and SMS apps mainly to contact family members and friends, respectively; whereas only 70% used call app to facilitate the purchase of farm input and 65% used it to get market-related information. Tobit regression analysis results showed that years of farming experience, awareness and knowledge of apps usage positively influenced the use of the mobile app at p<0.01. It was concluded that farmers' awareness of mobile apps was low and they minimally used these apps for farming activities. It's recommended that agricultural extension agencies and other relevant stakeholders should facilitate avenues to encourage the use of mobile phone apps for agricultural purposes among farmers.